SIRT1 and Estrogen Signaling Cooperation for Breast Cancer Onset and Progression - Liarte, Sergio; Alonso-Romero, José Luis; Nicolás, Francisco José (Frontiers in Endocrinology, 2018)
Breast cancer remains a significant female mortality cause. It constitutes a multifactorial disease for which research on environmental factors offers little help in predicting onset or progression. The pursuit for its foundations by analyzing hormonal changes as a motive for disease development, indicates that increased exposure to estrogens associates with increased risk. A prevalent number of breast cancer cases show dependence on the increased activity of the classic nuclear estrogen receptor (ER) for cell proliferation and survival. SIRT1 is a Type III histone deacetylase which is receiving increasing attention due to its ability to perform activities over relevant non-histone proteins and transcription factors. Interestingly, concomitant SIRT1 overexpression is commonly found in ER-positive breast cancer cases. Both proteins had been shown to directly interact, in a process related to altered intracellular signaling and aberrant transcription, then promoting tumor progression. Moreover, SIRT1 activities had been also linked to estrogenic effects through interaction with the G-protein coupled membrane bound estrogen receptor (GPER). This work aims to summarize present knowledge on the interplay between SIRT1 and ER/GPER for breast cancer onset and progression. Lastly, evidences on the ability of SIRT1 to interact with TGFß signaling, a concurrent pathway significantly involved in breast cancer progression, are reported. The potential of this research field for the development of innovative strategies in the assessment of orphan breast cancer subtypes, such as triple negative breast cancer (TNBC), is discussed.